Preparasi RNA Virus Mosaik Bergaris dari Tanaman Tebu Menggunakan Metode Tabung PCR - Tri Asmira Damayanti; Lilik Koesmihartono Putra (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Sugarcane streak mosaic virus (SCSMV) is a new emerging virus infecting sugarcane in Indonesia. The virus can be found almost in every sugarcane plantations in Java and it was known as sett-borne virus. Attempt to get virus-free seedling meet difficulties due to lacking an easy, and accurate detection method. SCSMV antiserum is not available yet commercially. Nucleic acid detection by RT-PCR also hampered difficulties in releasing RNA virus from sugarcane tissues. Here we reported the simple direct tube method with minor modification as the convenient way to provide total RNA template from infected sugarcane leaf, stalk and sheath for RT-PCR detection of SCSMV.Key words: RNA extraction, RT-PCR, SCSMV, tube PCR